Prevalence and risk factors of retinal vein occlusion: the Gutenberg Health Study. (1st June 2015) - Ponto, K. A.; Elbaz, H.; Peto, T.; Laubert‐Reh, D.; Binder, H.; Wild, P. S.; Lackner, K.; Pfeiffer, N.; Mirshahi, A.
Summary Objective To determine the age‐ and sex‐specific prevalence and determinants of retinal vein occlusions (RVOs) in a large population‐based German cohort. Methods The investigation included 15 010 participants (aged 35–74 years) from the Gutenberg Health Study. We determined the prevalence of RVO (central retinal vein occlusion [CRVO] and branch retinal vein occlusion [BRVO]) for the local population by assessing fundus photographs of 12 954 (86.3%; 49.8% women and 50.2% men) participants. Further, we analyzed the associations of RVO with cardiovascular, anthropometric, and ophthalmic parameters. Results The weighted prevalences of RVO, CRVO, and BRVO were 0.40%, 0.08%, and 0.32%, respectively. Men were 1.7 times more frequently affected by RVO than were women. Prevalence of RVO was 0.2% in participants aged 35–44 and 45–54 years, respectively, 0.48% in those aged 55–64 years, and 0.92% in those aged 65–74 years. Of persons with RVO, 91.5% had one or more cardiovascular risk factor or disease vs. 75.9% of persons without RVO. BRVO was associated with arterial hypertension (odds ratio 2.69, 95% confidence interval 1.27–5.70) and atrial fibrillation (3.37, 1.24–9.12) and CRVO with higher age (7.02, 1.63–30.19) and a family history of stroke (4.64, 1.18–18.25). Median visual acuity (base 10 logarithm of minimum angle of resolution) was 0.2 in persons with RVO vs. 0.05 in those without. Conclusion The prevalence of RVO in this German population was 0.4%, and men were 1.7 times more frequently affected than women. CRVO was associated with higher age and a family history of stroke, and BRVO was associated with arterial hypertension and atrial fibrillation.